Preparation method of halogen-free flame-retardant high-strength seaweed fiber

By blending electrospinning sodium alginate, sodium benzoate homotriazine modified polyvinyl alcohol and hexa-(aminophenoxy)cyclotriphosphazene hydrochloride, the problem of poor mechanical properties and flame retardant properties of traditional sodium alginate fibers is solved, and seaweed fibers with high strength and good flame retardant properties are achieved.

CN119465445BActive Publication Date: 2025-04-15SHANDONG HAIXIAN BIOMATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510058815.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-15
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The mechanical properties and flame retardancy of traditional sodium alginate fibers limit their practical application areas.

Method used

By blending electrospinning of sodium alginate, sodium benzoate homotriazine modified polyvinyl alcohol and hex-(aminophenoxy)cyclotriphosphazene hydrochloride, the cross-linking effect of sodium alginate and polyvinyl alcohol is achieved, and the mechanical properties and flame retardant properties of the fiber are improved.

Benefits of technology

The fracture strength and elongation of seaweed fibers are significantly improved, and their flame retardant properties are improved, showing higher limit oxygen index and lower peak combustion heat release rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The present invention relates to the field of fiber technology, and discloses a preparation method of halogen-free flame-retardant high-strength seaweed fiber. The present invention adds distilled water, sodium alginate, sodium benzoate-s-triazine-modified polyvinyl alcohol, and hexa-(aminophenoxy)-cyclotriphosphazene hydrochloride into a container, and after stirring and dissolving, spinning is performed by an electrostatic spinning machine to obtain halogen-free flame-retardant high-strength seaweed fiber. The sodium benzoate-s-triazine-modified polyvinyl alcohol contains a large amount of nitrogen-rich triazine flame-retardant groups, and forms a nitrogen-phosphorus flame-retardant system with the cyclotriphosphazene structure. When burning, a large amount of non-combustible gases such as nitrogen can be generated, and phosphoric acid substances are generated at the same time, which promotes the dehydration of the fiber matrix into carbon, so that the fiber has good flame retardant properties, showing a higher limiting oxygen index and a lower peak value of the combustion heat release rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fibers, in particular to a method for preparing halogen-free flame-retardant high-strength seaweed fibers. Background Art

[0002] Sodium alginate has good biocompatibility, biodegradability, non-toxicity and pollution-free, and has good spinnability. It can be spun with cellulose, polyvinyl alcohol, gelatin and other materials to form fibers, and is widely used. Traditional sodium alginate fibers have problems such as poor mechanical properties, and usually need to add cross-linking agents such as glutaraldehyde and calcium chloride to improve the mechanical strength of the fiber. And the flame retardancy of sodium alginate fibers is poor, which limits its practical application field. Polyvinyl alcohol is biodegradable and has excellent hydrophilicity. It has important applications in materials such as fibers and plastics. The patent with the authorization announcement number CN115094539B discloses a heat-insulating and flame-retardant sodium alginate / polyvinyl alcohol aerogel fiber and a preparation method thereof. Sodium alginate and polyvinyl alcohol are spun and freeze-dried to obtain aerogel fibers with good mechanical properties, flexibility, heat insulation and flame retardancy. However, the patent does not improve the compatibility between sodium alginate and polyvinyl alcohol, which is not conducive to improving the mechanical strength of the fiber. Summary of the invention

[0003] In order to solve the problem that sodium alginate and polyvinyl alcohol fibers have poor mechanical properties and flame retardancy, the present invention provides a method for preparing halogen-free flame-retardant high-strength alginate fibers.

[0004] The preparation method of halogen-free flame-retardant high-strength seaweed fiber comprises the following steps:

[0005] Step S1, add distilled water and polyvinyl alcohol to the reaction container, heat and stir to dissolve, then add 1.2-3% sodium hydroxide aqueous solution, cosolvent, 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine by mass fraction, react at 80-95°C for 12-18h, condense and reflux during the reaction, concentrate the solution until a large amount of precipitate is precipitated, wash the filter cake with ethanol after suction filtration, and dry to obtain sodium benzoate-s-triazine-modified polyvinyl alcohol. The reaction formula is: .

[0006] Step S2, add distilled water, sodium alginate, sodium benzoate-triazine-modified polyvinyl alcohol, and hexa(aminophenoxy)cyclotriphosphazene hydrochloride into a container, stir and dissolve, and then spin the obtained spinning solution through an electrospinning machine, control the spinning voltage to 30-40 kV, and the spinning solution flow rate to 0.2-0.7 mL / h to obtain halogen-free flame-retardant high-strength seaweed fiber.

[0007] Preferably, in step S1, the amount of polyvinyl alcohol used is 100 parts by weight, and the amount of 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine used is 2-6 parts by weight.

[0008] Preferably, the co-solvent in step S1 is tetrahydrofuran or 1,4-dioxane.

[0009] Preferably, in step S2, the amount of sodium alginate used is 100 parts by weight, the amount of sodium benzoate-triazine-modified polyvinyl alcohol used is 20-50 parts by weight, and the amount of hexa(aminophenoxy)cyclotriphosphazene hydrochloride used is 3-8 parts by weight.

[0010] Preferably, the preparation method of the hexa(aminophenoxy)cyclotriphosphazene hydrochloride is as follows: N,N-dimethylformamide, hexa(aminophenoxy)cyclotriphosphazene, and a hydrochloric acid solution with a mass fraction of 15-20% are added to a reaction container, and the solution is concentrated after stirring until a large amount of precipitate is precipitated, and the filter cake is washed with acetone after suction filtration and dried to obtain hexa(aminophenoxy)cyclotriphosphazene hydrochloride. The reaction formula is as follows: .

[0011] Beneficial effect: The present invention electrostatically spins sodium alginate, sodium benzoate s-triazine modified polyvinyl alcohol, and hexa-(aminophenoxy) cyclotriphosphazene hydrochloride to obtain halogen-free flame-retardant high-strength seaweed fiber. Hexa-(aminophenoxy) cyclotriphosphazene hydrochloride contains multiple amino hydrochloride cation structures, which can form anion-cation bonds with sodium carboxylate anions of sodium alginate and sodium carboxylate anions of sodium benzoate s-triazine modified polyvinyl alcohol, thereby realizing cross-linking of sodium alginate and polyvinyl alcohol, significantly improving the compatibility between the two, avoiding the poor compatibility of the two and affecting the mechanical properties of the fiber. At the same time, after chemical cross-linking, it is beneficial to improve the mechanical properties of the fiber, so that the seaweed fiber exhibits higher breaking strength and elongation at break.

[0012] The sodium benzoate isotriazine-modified polyvinyl alcohol of the present invention contains a large amount of nitrogen-rich triazine flame retardant groups, which form a nitrogen-phosphorus flame retardant system with the cyclotriphosphazene structure. When burned, a large amount of non-combustible gases such as nitrogen can be generated, and phosphoric acid substances can be generated at the same time, which promotes the dehydration of the fiber matrix into carbon, so that the fiber has good flame retardant properties, and shows a higher limiting oxygen index and a lower combustion heat release rate peak value. DETAILED DESCRIPTION

[0013] In order to make the purpose, technical solution and advantages of the invention more clearly understood, the present invention is further described in detail below in conjunction with examples. However, the content of the present invention is not limited to the following examples.

[0014] Hexa(aminophenoxy)cyclotriphosphazene was prepared according to the method of the document "Synthesis of Hexa(aminophenoxy)cyclotriphosphazene" in the journal "Inner Mongolia Science and Technology and Economy" No. 19, 2006. The structural formula is: .

[0015] According to the method of the journal J. Heterocyclic Chem., 48, 769 (2011); the literature "Complexes of iron(III) and chromium(III) salen and salophen Schiff bases with bridging 1,3,5-triazine derived multidirectional ligands", 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine was prepared. The structural formula is: .

[0016] Embodiment 1: A method for preparing halogen-free flame-retardant high-strength seaweed fiber, comprising the following steps:

[0017] (1) Add 70 mL of N,N-dimethylformamide, 4 g of hexa(aminophenoxy)cyclotriphosphazene, and 40 mL of a 15% hydrochloric acid solution into a reaction vessel, stir for 30 min, concentrate the solution, precipitate a large amount of precipitate, filter, wash the filter cake with acetone, and dry to obtain hexa(aminophenoxy)cyclotriphosphazene hydrochloride;

[0018] (2) Add 500 mL of distilled water and 60 g of polyvinyl alcohol to a reaction container, heat to 95° C., stir to dissolve, then add 120 mL of 2% by mass sodium hydroxide aqueous solution, 10 mL of 1,4-dioxane cosolvent, and 1.2 g of 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine, and react at 90° C. for 18 h. During the reaction, condense and reflux, concentrate the solution until a large amount of precipitate is precipitated, filter, wash the filter cake with ethanol, and dry to obtain sodium benzoate-triazine-modified polyvinyl alcohol;

[0019] (3) Add 2 L of distilled water, 100 g of sodium alginate, 20 g of sodium benzoate-triazine-modified polyvinyl alcohol, and 3 g of hexa(aminophenoxy)cyclotriphosphazene hydrochloride into a container, heat to 95 °C, stir to dissolve, and then spin the obtained spinning solution through an electrospinning machine. The spinning voltage is controlled to 30 kV and the spinning solution flow rate is controlled to 0.7 mL / h to obtain halogen-free flame-retardant high-strength seaweed fiber.

[0020] Embodiment 2: A method for preparing halogen-free flame-retardant high-strength seaweed fiber, comprising the following steps:

[0021] (1) Add 50 mL of N,N-dimethylformamide, 4 g of hexa(aminophenoxy)cyclotriphosphazene, and 30 mL of 20% hydrochloric acid solution into a reaction container, stir for 40 min, concentrate the solution, precipitate a large amount of precipitate, filter, wash the filter cake with acetone, and dry to obtain hexa(aminophenoxy)cyclotriphosphazene hydrochloride;

[0022] (2) Add 600 mL of distilled water and 60 g of polyvinyl alcohol to a reaction container, heat to 95° C., stir to dissolve, then add 100 mL of 3% sodium hydroxide aqueous solution, 20 mL of tetrahydrofuran as a cosolvent, and 2 g of 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine, and react at 80° C. for 18 h. During the reaction, condense and reflux, concentrate the solution until a large amount of precipitate is precipitated, filter, wash the filter cake with ethanol, and dry to obtain sodium benzoate-triazine-modified polyvinyl alcohol;

[0023] (3) Add 2.5 L of distilled water, 100 g of sodium alginate, 30 g of sodium benzoate-triazine-modified polyvinyl alcohol, and 4.5 g of hexa-(aminophenoxy)cyclotriphosphazene hydrochloride into a container, heat to 95 °C, stir to dissolve, and then spin the obtained spinning solution through an electrospinning machine. Control the spinning voltage to 30 kV and the spinning solution flow rate to 0.5 mL / h to obtain halogen-free flame-retardant high-strength seaweed fiber.

[0024] Embodiment 3: A method for preparing halogen-free flame-retardant high-strength seaweed fiber, comprising the following steps:

[0025] (1) Add 600 mL of distilled water and 60 g of polyvinyl alcohol to a reaction container, heat to 95° C., stir to dissolve, then add 140 mL of 3% sodium hydroxide aqueous solution, 20 mL of tetrahydrofuran as a cosolvent, and 2.8 g of 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine, and react at 95° C. for 12 h. During the reaction, condense and reflux, concentrate the solution until a large amount of precipitate is precipitated, filter, wash the filter cake with ethanol, and dry to obtain sodium benzoate-s-triazine-modified polyvinyl alcohol;

[0026] (2) Add 3L of distilled water, 100g of sodium alginate, 40g of sodium benzoate-triazine-modified polyvinyl alcohol, and 6g of hexa(aminophenoxy)cyclotriphosphazene hydrochloride (prepared in the same manner as in Example 1) into a container, heat to 95°C, stir to dissolve, and then spin the obtained spinning solution through an electrospinning machine. The spinning voltage is controlled to be 30kV and the spinning solution flow rate is controlled to be 0.5mL / h to obtain halogen-free flame-retardant high-strength seaweed fiber.

[0027] Embodiment 4: A method for preparing halogen-free flame-retardant high-strength seaweed fiber, comprising the following steps:

[0028] (1) Add 600 mL of distilled water and 60 g of polyvinyl alcohol to a reaction container, heat to 95° C., stir to dissolve, then add 150 mL of 3% sodium hydroxide aqueous solution, 20 mL of 1,4-dioxane cosolvent, and 3.6 g of 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine, and react at 90° C. for 18 h. During the reaction, condense and reflux, concentrate the solution until a large amount of precipitate is precipitated, filter, wash the filter cake with ethanol, and dry to obtain sodium benzoate-s-triazine-modified polyvinyl alcohol;

[0029] (2) Add 3L of distilled water, 100g of sodium alginate, 50g of sodium benzoate-triazine-modified polyvinyl alcohol, and 8g of hexa(aminophenoxy)cyclotriphosphazene hydrochloride (prepared in the same manner as in Example 1) into a container, heat to 95°C, stir to dissolve, and then spin the obtained spinning solution through an electrospinning machine. The spinning voltage is controlled to 40kV and the spinning solution flow rate is controlled to 0.2mL / h to obtain halogen-free flame-retardant high-strength seaweed fiber.

[0030] Comparative Example 1: Add 2L of distilled water, 100g of sodium alginate, and 20g of sodium benzoate-triazine-modified polyvinyl alcohol (prepared in the same manner as in Example 1) into a container, heat to 95°C, stir and dissolve, and then spin the obtained spinning solution through an electrospinning machine. The spinning voltage is controlled to 30kV and the spinning solution flow rate is 0.7mL / h to obtain seaweed fiber.

[0031] Comparative Example 2: Add 2L of distilled water, 100g of sodium alginate, 20g of polyvinyl alcohol, and 3g of hexa-(aminophenoxy)cyclotriphosphazene hydrochloride (prepared in the same manner as in Example 1) into a container, heat to 95°C, stir and dissolve, and then spin the obtained spinning solution through an electrospinning machine. The spinning voltage is controlled to 30kV and the spinning solution flow rate is 0.7mL / h to obtain seaweed fiber.

[0032] Comparative Example 3: (1) Add 500 mL of distilled water and 60 g of polyvinyl alcohol to a reaction vessel, heat to 95 °C, stir to dissolve, then add 120 mL of 2% sodium hydroxide aqueous solution, 10 mL of 1,4-dioxane cosolvent, 1.2 g of 6-chloro-N,N'-diphenyl-1,3,5-triazine-2,4-diamine (CAS No. 1973-09-7, structural formula: ), react at 90°C for 18h, condense and reflux during the reaction, concentrate the solution until a large amount of precipitate is precipitated, filter and wash the filter cake with ethanol, and dry to obtain triazine-modified polyvinyl alcohol;

[0033] (2) Add 2 L of distilled water, 100 g of sodium alginate, 20 g of triazine-modified polyvinyl alcohol, and 3 g of hexa(aminophenoxy)cyclotriphosphazene hydrochloride (prepared in the same manner as in Example 1) into a container, heat to 95° C., stir to dissolve, and then spin the obtained spinning solution through an electrospinning machine. The spinning voltage is controlled to be 30 kV and the spinning solution flow rate is controlled to be 0.7 mL / h to obtain seaweed fibers.

[0034] The mechanical strength of seaweed fiber was tested by an electronic single fiber strength tester, with a clamping distance of 20 mm, a pre-tension of 0.3 cN, and a tensile speed of 20 mm / min. Each group of samples was tested 10 times and the average value was taken.

[0035] The limiting oxygen index of seaweed fiber is tested according to the national standard GB / T 5454-1997.

[0036] The combustion performance of seaweed fiber was tested by cone calorimeter with a heat flux of 35kW / m 2 .

[0037] Table 1: Test results of various embodiments and comparative examples

[0038]

[0039] The seaweed fiber of embodiment 1-embodiment 4 has higher breaking strength and elongation at break, and the limiting oxygen index reaches 28.7-34.9%, and the peak value of the combustion heat release rate is only 51.3-114.8 W / g, showing good mechanical properties and flame retardant properties. Mainly because sodium benzoate s-triazine modified polyvinyl alcohol and six-(aminophenoxy) cyclotriphosphazene hydrochloride are added, six-(aminophenoxy) cyclotriphosphazene hydrochloride contains multiple amino hydrochloride cationic structures, which can interact with the sodium carboxylate anion of sodium alginate and the sodium carboxylate anion of sodium benzoate s-triazine modified polyvinyl alcohol to form an anionic and cationic bond, thereby realizing the cross-linking of sodium alginate and polyvinyl alcohol, significantly improving the compatibility between the two, avoiding affecting the mechanical properties of the fiber due to poor compatibility, and at the same time, through chemical cross-linking, it is beneficial to improve the mechanical properties of the fiber, so that the seaweed fiber shows higher breaking strength and elongation at break. In addition, the nitrogen-rich triazine flame retardant group in polyvinyl alcohol forms a nitrogen-phosphorus flame retardant system with the cyclotriphosphazene structure. When burned, it can produce a large amount of non-combustible gases such as nitrogen, and at the same time produce phosphoric acid substances, which promote the dehydration of the fiber matrix into carbon, so that the fiber has excellent flame retardant properties, showing a higher limiting oxygen index and a lower peak combustion heat release rate.

[0040] Compared with Example 1, the seaweed fiber of Comparative Example 1 does not contain hexa(aminophenoxy)cyclotriphosphazene hydrochloride, and thus does not play an ionic cross-linking role. In addition, the compatibility between sodium alginate and polyvinyl alcohol is poor, resulting in poor mechanical properties of the seaweed fiber, a low limiting oxygen index, a high peak value of the combustion heat release rate, and poor flame retardancy.

[0041] The polyvinyl alcohol added in Comparative Example 2 does not contain a sodium carboxylate structure and cannot undergo ionic cross-linking with sodium alginate through hexa-(aminophenoxy)cyclotriphosphazene hydrochloride, resulting in poor compatibility between polyvinyl alcohol and sodium alginate. The breaking strength and elongation at break of the seaweed fiber are lower than those in Example 1, and the polyvinyl alcohol does not contain a nitrogen-rich triazine flame retardant group, resulting in poor flame retardancy of the fiber.

[0042] In Comparative Example 3, 6-chloro-N,N'-diphenyl-1,3,5-triazine-2,4-diamine is reacted with polyvinyl alcohol. The obtained triazine-modified polyvinyl alcohol does not contain a sodium carboxylate anion structure and cannot undergo ionic cross-linking with sodium alginate through hexa-(aminophenoxy)cyclotriphosphazene hydrochloride, resulting in poor compatibility between polyvinyl alcohol and sodium alginate, and the breaking strength and elongation at break of the seaweed fiber are lower than those in Example 1.

[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing halogen-free flame-retardant high-strength seaweed fiber, characterized in that: The following steps are involved: Step S1, adding distilled water and polyvinyl alcohol to a reaction container, heating and stirring to dissolve, then adding sodium hydroxide aqueous solution, cosolvent, and 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine, concentrating the solution after the reaction, precipitating a precipitate, filtering, washing the filter cake with ethanol, and drying to obtain sodium benzoate-s-triazine-modified polyvinyl alcohol; Step S2, adding distilled water, sodium alginate, sodium benzoate-s-triazine-modified polyvinyl alcohol, and hexa-(aminophenoxy)cyclotriphosphazene hydrochloride into a container, stirring and dissolving, spinning the obtained spinning solution through an electrospinning machine, controlling the spinning voltage to 30-40 kV, and the spinning solution flow rate to 0.2-0.7 mL / h, to obtain halogen-free flame-retardant high-strength seaweed fiber; The preparation method of the hexa(aminophenoxy)cyclotriphosphazene hydrochloride is as follows: N,N-dimethylformamide, hexa(aminophenoxy)cyclotriphosphazene and hydrochloric acid solution are added to a reaction container, the solution is concentrated after stirring to precipitate a precipitate, the filter cake is washed with acetone after suction filtration, and dried to obtain hexa(aminophenoxy)cyclotriphosphazene hydrochloride; The mass fraction of the hydrochloric acid solution is 15-20%.

2. The method for preparing the halogen-free flame-retardant high-strength seaweed fiber according to claim 1, characterized in that: In the step S1, the amount of polyvinyl alcohol used is 100 parts by weight, and the amount of 2-chloro-4,6-di(4-aminobenzoic acid)-1,3,5-triazine used is 2-6 parts by weight.

3. The method for preparing the halogen-free flame-retardant high-strength seaweed fiber according to claim 1, characterized in that: In the step S1, the co-solvent is tetrahydrofuran or 1,4-dioxane.

4. The method for preparing the halogen-free flame-retardant high-strength seaweed fiber according to claim 1, characterized in that: The mass fraction of the sodium hydroxide aqueous solution in step S1 is 1.2-3%.

5. The method for preparing halogen-free flame-retardant high-strength seaweed fiber according to claim 1, characterized in that: The step S1 is reacted at 80-95° C. for 12-18 hours.

6. The method for preparing halogen-free flame-retardant high-strength seaweed fiber according to claim 1, characterized in that: In the step S2, the amount of sodium alginate used is 100 parts by weight, the amount of sodium benzoate-triazine-modified polyvinyl alcohol used is 20-50 parts by weight, and the amount of hexa(aminophenoxy)cyclotriphosphazene hydrochloride used is 3-8 parts by weight.

Citation Information

Patent Citations

  • A heat-insulating and flame-retardant sodium alginate / polyvinyl alcohol aerogel fiber and its preparation method

    CN115094539B

  • Sodium alga acid flame retardant fibers loaded with metal ions and manufacture method thereof

    CN105821523A

  • Modified fireproof homogeneous plate and production process thereof

    CN114478061A